The Effect Of The Talking Stick Type Cooperative Learning Model On The Geography Learning Outcomes Of Grade XII Students Tembilahan 2nd High School - Nova Yulizar; Syafri Anwar (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine the effect of the Talking Stick learning model on the geography learning outcomes of class XII students of SMAN 2 Tembilahan. This type of research is quantitative with a quasi-experimental approach. The population of this study comprised all class XII students (N = 90), with the research sample consisting of class XII A (experimental; N = 30) and XII B (control; N = 30). The research instrument was a multiple-choice test. Before the test instrument was used in the research, a pretest was conducted to assess its quality and feasibility. The instrument test was conducted to determine the difficulty of the questions and the discriminative power. The data analysis techniques used in the study included the difference power test, difficulty level test, normality test, homogeneity test, t-test, and N-Gain test, using SPSS Version 20. From the results of data analysis on the effect of the application of the Talking Stick learning model on the Geography learning outcomes of class XII students of SMAN 2 Tembilahan, it can be concluded that the Geography learning outcomes of students in the Experimental class, which was taught using the Talking Stick learning model with a sample of 30 students had an average Posttest value of 80.22. With. The Geography learning outcomes of students in the control class, taught using the Conventional learning model with a sample of 30 students, had an average posttest score of 75.60. Based on the results of the t-test above, the results were obtained that t count> t Table, namely 4.697> 1.69 and a significance level <0.05, namely 0.000, so it can be concluded that the hypothesis H1 is accepted or H0 is rejected. It can be concluded that there is a significant difference between the experimental class using the Talking Stick learning model and the control class without the Talking Stick learning model.